Double Trouble: an observational study of thyroid dysfunction in South Indian subjects with type 2 diabetes - R. Anil Kumar; Lalitha R; Surekha B. Shetty (International Journal of Medical Research and Review, 2017)
Objective: Studies conducted in subjects with type 2 diabetes have shown increased prevalence of overt hypothyroidism and subclinical hypothyroidism. Hence, we designed a study to find out the prevalence of thyroid dysfunction in south Indian subjects with type 2 diabetes.Research Design and Methods: 400 subjects with type 2 diabetes attending the out-patient department of Karnataka Institute of Endocrinology and Research, Bangalore were randomly selected. 200 relatives who accompanied the subjects without diabetes were recruited as controls. BMI, waist circumference, blood pressure, fasting plasma glucose, post prandial plasma glucose, HbA1c, lipid profile, and thyroid profile of these subjects were determined.Results: 400 subjects with type 2 diabetes and 200 subjects without diabetes were included in the study. They were in the age group of 25 to 75 years. Thyroid dysfunction was present in 13% of non diabetic controls. Subclinical hypothyroidism was present in 7%, overt hypothyroidism in 5% and hyperthyroidism in 1% of the controls. Thyroid dysfunction was present in 24% of subjects with type 2 diabetes. Subclinical hypothyroidism was present in 11.25%, overt hypothyroidism in 12% and hyperthyroidism in 0.75% of the 400 subjects with type 2 diabetes.Conclusions: Hypothyroidism especially subclinical hypothyroidism is more common in south Indian subjects with type 2 diabetes. Hence, it is indispensable to investigate for thyroid dysfunction in subjects with type 2 diabetes. Failure to recognize the presence of thyroid dysfunction may be a primary cause of poor glycemic control often encountered in some subjects with type 2 diabetes, despite appropriate anti diabetic therapy. This highlights the need for the routine evaluation of thyroid function in subjects with type 2 diabetes.